Was there too little entry during the Dot Com Era?☆ - GOLDFARB, B; KIRSCH, D; MILLER, D (Journal of Financial Economics, 2007)
We present four stylized facts about the Dot Com Era: (1) there was a widespread belief in a Get Big Fast business strategy, (2) the increase and decrease in public and private equity investment was most prominent in the Internet and information technology sectors, (3) the survival rate of dot com firms is on par with or higher than other emerging industries, and (4) firm survival is independent of private equity funding. To connect these findings we offer a herding model that accommodates a divergence between the information and incentives of venture capitalists and their investors. A Get Big Fast belief cascade could have led to overly focused investment in too few Internet startups and, as a result, too little entry.